CONSTRUCTION OF NATION AND NATIONALISM IN 4 INDONESIAN NOVELS IN EUROPE - Candra Rahma Wijaya Putra; Rose Fitria Lutfiana (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2020)
This study aims to understand the concept of nation and nationalism through four literary works with a European background. The approach of literary sociology in this study is used to look for forms of Indonesian nationalism in Europe. The aim is to find the source of self-depiction as an important element in constructing the concept of the nation. The results showed that the self-image as an Indonesian identity was aimed at citizenship, history, culture (language and food), race (ethnicity), and religion. Collective awareness about citizenship, history, culture, and race refers to the locally imagined community, namely the Indonesian people. Religion refers to the universal community. The five elements are at the same time a source of nationalism, both the nation in understanding local and universal communities.Penelitian ini bertujuan untuk memahami konsep bangsa dan nasionalisme melalui empat karya sastra berlatar Eropa. Pendekatan sosiologi sastra dalam penelitian ini digunakan untuk mencari pembeda nasionalisme Indonesia di Eropa. Tujuannya adalah mencari sumber penggambaran diri sebagai unsur penting dalam mengkonstruksi konsep bangsa. Hasil penelitian menunjukan bahwa gambaran diri sebagai identitas keindonesiaan ditujukan dalam kewarganegaraan, sejarah, budaya (bahasa dan makanan), ras (etnis), dan agama. Kesadaran kolektif tentang kewarganegaraan, sejarah, budaya, dan ras merujuk pada komunitas terbayang lokal, yaitu bangsa Indonesia. Agama merujuk pada komunitas universal. Kelima unsur tersebut sekaligus sebagai sumber nasionalisme, baik bangsa dalam pemahaman komunitas lokal maupun universal.